Cinema and Pragmatism: a Reflection on the Signic Genesis in Cinematographic Art - Santos, Marcelo Moreira (Signs - International Journal of Semiotics, 2009)
This article aims to discuss the importance and urgency of Charles S. Peirce's philosophy to understand the creative genesis of movie making. This is a reflection on the ontology and possible cinematographic epistemology through Peircean semiotics. Methodologically, we discuss the phenomenology of the Metropolis as a fulcrum for the development of a language and of an aesthetics such as the aesthetic dimension possible to be achieved within the language of cinema, by observing the hybrid character of such communication and the behavior of the movie makers in relation to those particular possibilities of aesthetics, and by emphasizing the importance of pragmatism in the materalization of a movie through a triadic thought, from the imaginary ideal at first, the try out of possibilities as a second stage, towards a definition of the idea, to the externalization and development of a movie as language. This triad has the Peircean categories – Firstness, Secondness and Thirdness – as its conceptual ground, and yet keeps many correspondences with the poetics of Aristotle, allowing, thus, a reflection between Peirce and the great Greek philosopher.